MPRO: A Professionalism Curriculum to Enhance the Professional Identity Formation of University Premedical Students. Issue 1 (1st January 2021) - Merlo, Gia; Ryu, Hanjun; Harris, Toi B.; Coverdale, John
ABSTRACT: Limited opportunities exist for university premedical students to gain exposure to the realities of clinical practice through physician shadowing or through a formal curriculum. Medical Professionalism and Observership utilizes didactics, reflective writing, small- and large- group discussions, and clinical observerships to enhance the process of professional identity formation during a critical developmental window of late- adolescence. The pilot semester included a sample of 135 students, all in their sophomore, junior, or senior years of study at Rice University. Students were selected through an application process and paired with physicians at Houston Methodist Hospital based on specialty preference and availability. Students were required to participate in biweekly lectures and discussions and to submit a weekly reflection on topics discussed in the course and their shadowing experiences. Student evaluations were administered to survey changes in students' knowledge and perceptions of the curriculum. Selected reflections were read for evidence of professional identity formation. Lectures increased students' exposure to core competencies within the medical profession and influenced their desire to become physicians. Reflective writings demonstrated integration of these core competencies into the professional identity of students. Structured reflection and didactics, when coupled with physician shadowing, appear to promote integration of the values, beliefs, and attitudes of medical professionalism. Future studies should seek to demonstrate how such a curriculum affects professional identity formation through established measures, and to assess whether such a curriculum may influence students' preparedness for medical training and practice as they progress along their careers.